THE EFFECT OF IN-GAME ADVERTISING AS A MARKETING TECHNIQUE ON THE PURCHASING BEHAVIOR OF GENERATION Z IN TURKEY - ADIGÜZEL, SELMİNAZ (Universitas Airlangga, 2024)
The purpose of this study is to investigate the effect of in-game advertisements, which are a marketing technique, on the purchasing behaviors of Muslim youth and the purchasing behaviors of these youth in Generation Z. The survey of the study was prepared by Betül Başer and Özgün Arda Kuş, a 31-question survey was applied to 250 volunteer students by e-mail after receiving permission from the researchers and receiving approval from the ethics committee. The survey data was uploaded to the SPSS 25 program and the frequencies and percentages of the data were obtained. In the study, analyses were conducted using quantitative research methods such as variance analysis (ANOVA), t-test and Tukey test. According to the results of the research, significant differences were determined among Generation Z according to gender, age and education level. In order to make Islamic production and investments according to new trends, it is necessary to know the characteristics of the generations well and to develop Islamic applications and software suitable for these characteristics. Since Generation Z cares about games and the advertisements they encounter during the game, it is important for Islamic investments and productions to be developed in a way that has Islamic characteristics.